CORPORATE CYBERESPIONAGE: IDENTIFICATION AND PREVENTION PART 2. Issue 6 (1st December 2020) - Mitchell, Brian
ABSTRACT: The purpose of this paper is to present an argument for a methodology to detect and prevent cyber-based corporate espionage. The focus of this paper will be on the human domain and how it affects control measures in the electronic and physical domain of cybersecurity. The reason for this approach is because the human domain has consistently been identified as the irrational and unpredictable component in cybersecurity. Human actions, when related to cyber-based corporate espionage, cannot be described through rudimentary factors supporting causation for "betrayal" and the motivation to compromise proprietary technology and economic information belonging to a business entrusting its secrets with an employee. The underlying issue is about how to identify a potential actor willing to compromise their "integrity" in exchange for personal gain or personal interest even when the penalty will be far greater than the reward. The next step is to propose preventative measures to either dissuade such behavior or expose a threat actor intending to compromise a corporation's information assets.